A Novel Validated Recurrence Stratification System Based on 18F-FDG PET/CT Radiomics to Guide Surveillance After Resection of Pancreatic Cancer - Wei, Miaoyan; Gu, Bingxin; Song, Shaoli; Zhang, Bo; Wang, Wei; Xu, Jin; Yu, Xianjun; Shi, Si (Frontiers in Oncology, 2021)
Objective: Despite the heterogeneous biology of pancreatic cancer, similar surveillance schemas have been utilized. Identifying the high recurrence risk population and conducting prompt intervention may improve prognosis and prolong overall survival. Methods: A total of 156 resectable pancreatic cancer patients who underwent 18F-FDG PET/CT from January 2013 to December 2018 were retrospectively reviewed. The patients were categorized into a training cohort (n=109) and a validation cohort (n=47). LIFEx software was used to extract radiomic features from PET/CT. The risk stratification system was based on predictive factors for recurrence, and the index of prediction accuracy was used to reflect both the discrimination and calibration. Results: Overall, 7 risk factors consisting of the rad-score and clinical variables that were significantly correlated with relapse were incorporated into the final risk stratification system. The 1-year recurrence-free survival differed significantly among the low-, intermediate-, and high-risk groups (85.5%, 24.0%, and 9.1%, p < 0.0001). The C-index of the risk stratification system in the development cohort was 0.890 (95% CI, 0.835-0.945). Conclusion: The 18F-FDG PET/CT-based radiomic features and clinicopathological factors demonstrated good performance in predicting recurrence after pancreatectomy in pancreatic cancer patients, providing a strong recommendation for an adequate adjuvant therapy course in all patients. The high-risk recurrence population should proceed with closer follow-up in a clinical setting.